Dynamic Analysis of the Gait Cycle for Normal and Abnormal Subjects - Abass, Sadiq J.; Faihan, Basma A. (Nahrain University College of Engineering Journal, 2017)
Identification of pathological gait is the most direct application of gait analysis. The purpose of the study is to investigate the dynamics of human walking over a complete gait cycle. Level-walking experiments were performed by two-dimensional (2D) motion analysis using a digital video camera (Sony, 25 Hz) and two force plates. Kinematic data were obtained from the trajectories of 7 reflective markers using SkillSpector software (ver. 1.2.4). MATLAB software (ver. 8.1) has been adopted in this work to obtain Pedotti diagram and for inverse dynamics computations. Digital low pass Butterworth filter with zero phase-shift and cut-off frequency of 4.5 Hz was used. Joints' angular displacement, forces, and moments were obtained during gait cycle. The study was made on fourteen healthy volunteers (10 males and 4 females); a male with cerebral palsy, and an old female underwent unilateral knee arthroplasty. These data can be used as standard measures in pathology studies, as input to theoretical joint models, and as input to mechanical joint simulators.